Preclinical evaluation of cancer immune therapy using patient‐derived tumor antigen‐specific T cells in a novel xenograft platform. Issue 2 (2nd February 2021) - Shenoy, Gautam N; Greene, Christopher J; Bhatta, Maulasri; Baroja, Miren L; Loyall, Jenni L; Balu‐Iyer, Sathy V; Kelleher, Raymond J; Carreno, Beatriz M; Linette, Gerald P; Shultz, Leonard D; Bankert, Richard B
Abstract: Objectives: With a rapidly growing list of candidate immune‐based cancer therapeutics, there is a critical need to generate highly reliable animal models to preclinically evaluate the efficacy of emerging immune‐based therapies, facilitating successful clinical translation. Our aim was to design and validate a novel in vivo model (called Xenomimetic or 'X' mouse) that allows monitoring of the ability of human tumor‐specific T cells to suppress tumor growth following their entry into the tumor. Methods: Tumor xenografts are established rapidly in the greater omentum of globally immunodeficient NOD‐ scid IL2Rγ null (NSG) mice following an intraperitoneal injection of melanoma target cells expressing tumor neoantigen peptides, as well as green fluorescent protein and/or luciferase. Changes in tumor burden, as well as in the number and phenotype of adoptively transferred patient‐derived tumor neoantigen‐specific T cells in response to immunotherapy, are measured by imaging to detect fluorescence/luminescence and flow cytometry, respectively. Results: The tumors progress rapidly and disseminate in the mice unless patient‐derived tumor‐specific T cells are introduced. An initial T cell‐mediated tumor arrest is later followed by a tumor escape, which correlates with the upregulation of the checkpoint molecules programmed cell death‐1 (PD‐1) and lymphocyte‐activation gene 3 (LAG3) on T cells. Treatment with immune‐based therapies that target these checkpoints, such as anti‐PD‐1 antibody (nivolumab) or interleukin‐12 (IL‐12), prevented or delayed the tumor escape. Furthermore, IL‐12 treatment suppressed PD‐1 and LAG3 upregulation on T cells. Conclusion: Together, these results validate the X‐mouse model and establish its potential to preclinically evaluate the therapeutic efficacy of immune‐based therapies. Abstract : We have designed and validated a first‐of‐its‐kind xenograft model, the Xenomimetic Mouse (X‐mouse) model, that has the ability to rapidly and reliably evaluate immune‐based therapies for cancer treatment using patient‐derived tumor‐specific T cells. Our model offers multiple advantages over existing preclinical models including but not limited to easy, accurate and quick measurement of tumor burden, monitoring changes in T‐cell phenotypes at the single cell level and rapid turnaround times. By validating the X‐mouse model using established clinically relevant immune‐based therapies, we demonstrate that it has potential to be a robust preclinical tool that will be of great utility to investigators involved in the development of immunotherapeutic targets and therapeutics for cancer treatment.